On LAO Testing of Multiple Hypotheses for Pair of Objects - Haroutunian, Evgueni A .; Hakobyan, Parandzem M. (Mathematical Problems of Computer Science, 2021)
Many hypotheses testing for a model consisting of two independent by functioning objects is considered. It is known that M(¸ 2) probability distributions are given and objects independently of other follows to one of them. The matrix of asymptotic interdependencies (reliability{reliability functions) of all possible pairs of the error probability exponents (reliabilities) in optimal testing for this model is studied. This problem was introduced (and solved for the case with two given probability distributions) by Ahlswede and Haroutunian. The situation with three hypotheses was examined by Haroutunian and Hakobyan.